THE MECHANISMS OF DEVELOPMENT AND EDUCATIONAL ADMINISTRATION INNOVATION IN THE EDUCATIONAL SANDBOX OF CHANTHABURI PROVINCE - Chansongsaeng, Arungiat; Surgrugsa, Narin; Warabamrungkul, Theerangkoon; Saitong, Waranut; Sahutat, Atchara; Sukkasi, Chatchai; Munya, Tuenjai; Kunrat, Thida; Suksiripannarut, Pantawit (Journal of MCU Nakhondhat, 2026)
This research aimed to (1) develop mechanisms for educational administration development and innovation in the Educational Sandbox of Chanthaburi Province and (2) implement and drive these mechanisms within the local educational context. The research employed a participatory action research (PAR) approach integrated with exploratory factor analysis (EFA) to ensure collaborative engagement and empirical validation. The sample consisted of 500 participants representing key educational stakeholders in the province. The implementation process followed four iterative stages: planning, action, observation, and reflection, and was conducted through two workshops, involving 104 participants in the first workshop and 176 participants in the second. Research instruments included interviews, questionnaires, observation forms, and focus group discussions, enabling comprehensive quantitative and qualitative data collection. The findings revealed that the mechanisms for educational administration development and innovation in the Educational Sandbox of Chanthaburi Province comprised three main dimensions, each consisting of three components. The development mechanism dimension included (1) change management toward achieving the Sustainable Development Goals, (2) professional competency development, and (3) holistic and area-based academic administration. The driving strategy consisted of (1) appreciative inquiry processes, (2) participatory administration through network partnerships, and (3) research and development. The development process dimension comprised (1) knowledge management, (2) evaluation culture, and (3) student learning outcomes. Furthermore, the provincial-level development mechanisms involved educational supervisors, school administrators, and university lecturers, while the school-level development mechanisms comprised two key entities: (1) school boards and (2) the quinquelateral collaborative network for educational promotion and innovation. In addition, educational administration innovation at the school level was implemented through four sequential stages: (1) designing an outcome-based model grounded in student learning outcomes, (2) developing strategic implementation plans, (3) establishing standards, criteria, and indicators, and (4) refining the outcome-based model grounded in student learning outcomes. These findings provide empirical evidence and practical implications for advancing sustainable educational administration development and innovation in educational innovation areas.